Daya Saing Ekspor Nanas dan Produk Olahan Nanas Indonesia di Pasar Global - Anna Dwi Putri; Tri Pujiana; Abu Haris Husain; Vinni Aurelia Salsabila (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Pineapple production in Indonesia experienced a significant increase, reaching 3,156,576 tons in 2023. This highlights the strong potential of this horticultural commodity to be developed as a leading export product. However, competition from major producing countries such as Costa Rica, the Philippines, and Brazil presents a considerable challenge to strengthening Indonesia's position in the global market. In response, this study aims to evaluate the performance and competitiveness of Indonesia’s pineapple exports, including processed pineapple products. The research employs a descriptive quantitative approach using the Revealed Comparative Advantage (RCA) and Index of Specialization Performance (ISP) methods. Data were obtained from the Food and Agriculture Organization (FAO) covering the period from 2000 to 2023. The analysis reveals that Indonesia has a comparative advantage in exporting canned pineapples and pineapple juice concentrate, as evidenced by RCA values exceeding one. On the other hand, fresh pineapples and pineapple juice have RCA values below one, suggesting a lack of comparative advantage in these two product categories. In terms of ISP, fresh pineapples, pineapple juice, and juice concentrate are in the maturity stage, with ISP values above 0.8, while canned pineapples are still in the growth stage with an ISP value of 0.75. These findings reinforce the competitive position of Indonesian pineapples in the global market and provide a strategic basis for developing a more export-oriented national pineapple industry.